Deteksi Dini Faktor Risiko Penyakit Kardiovaskuler pada Pegawai Rektorat Universitas Mataram - Ida Ayu Eka Widiastuti; Rifana Cholidah; Gede Wira Buanayuda; Ida Bagus Alit (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
Currently, the number of non-communicable diseases (PTM) is quite large and causes considerable morbidity and mortality. Globally PTM the number one cause of death every year is heart disease and blood vessels (cardiovascular). Data from the World Health Organization (WHO) states that more than 17 million people worldwide die from heart and blood vessel disease. Based on data from Riset Kesehatan Dasar (Riskesdas) in 2018, the incidence of heart and blood vessel disease has increased from year to year. At least, 15 out of 1000 people, or about 2,784,064 individuals in Indonesia suffer from heart disease. Cardiovascular disease often attacks productive age. Early detection is very important as a primary and secondary prevention of cardiovascular disease. The participants of this activity were 32 employees of the Mataram University Rectorate. Early detection of risk factors for cardiovascular disease is carried out through several tests: (1) anthropometric examinations, including body weight, height, body mass index, waist circumference, and body fat percentage, (2) blood pressure, and (3) blood samples examintaion to check fasting blood sugar levels and lipid profiles, which include triglyceride levels, total cholesterol, HDL cholesterol, and LDL cholesterol. From the results of the activity, it was found that the mean value of all types of examinations was abnormal, except for the levels of triglycerides and total cholesterol. Thus, in general, it can be said that participants have a high enough risk factor for cardiovascular disease.